2019
DOI: 10.1248/bpb.b19-00652
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Renal Clearance of Vancomycin in Hematologic Malignancy Patients

Abstract: The pharmacokinetics of vancomycin (VAN) was retrospectively examined based on trough concentrations at large scale to identify pharmacokinetic differences between Japanese hematologic malignancy and non-malignancy patients. Data from 261 hematologic malignancy patients and 261 non-malignancy patients, including the patient's background, VAN dose, and pharmacokinetics of VAN estimated by an empirical Bayesian method, were collected and analyzed. Our results showed significantly higher values for VAN clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…This issue has gained increasing attention. Previous studies have shown that there is a significant correlation between haematologic malignancy and ARC expression, and haematologic malignancy is highly likely to develop into ARC 7,11 . There have been vancomycin haematologic malignancy PPK studies 9,10,12 and ARC PPK studies 13‐15 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…This issue has gained increasing attention. Previous studies have shown that there is a significant correlation between haematologic malignancy and ARC expression, and haematologic malignancy is highly likely to develop into ARC 7,11 . There have been vancomycin haematologic malignancy PPK studies 9,10,12 and ARC PPK studies 13‐15 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Previously, we compared VAN pharmacokinetic parameters of non-malignancy patients and hematological malignancy patients by multiple regression analysis using propensity score matching, and found that CL VAN is effected by hematological malignancy. 23) Therefore, we concluded that the presence of malignant tumor was one factors affecting CL VAN , regardless of hematological malignancy or solid malignant tumor. A partial regression of each stage obtained by adjusting the patient background using the propensity score matching method for patients with solid malignant tumors is generally considered to be clinically significant, since the average value of CL VAN of non-malignancy patients is approximately 0.05 L/hr/kg.…”
Section: Discussionmentioning
confidence: 82%
“…A population pharmacokinetic parameter set for Japanese adult patients 26) was adopted as described previously. 23)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is important to evaluate the risk for ARC in these patients before starting the treatment and to design the antibiotic administration appropriately, there is no report for ARC in patients with malignancy. However, some animal and human studies have reported increased clearance of VCM in malignancies 13,14 . We hypothesized that ARC is a common phenomenon in patients with haematopoietic malignancies, as well as in critically ill patients.…”
Section: What Is Known and Objectivementioning
confidence: 95%